The Effect of Guided Discovery Model on Sociology of Religion Courses in Improving Students' Critical Thinking Skills - Gustina Gustina; Ardimen Ardimen; Zakirman Zakirman; Cut Afrina (STAI Hubbulwathan Duri, 2022)
Critical thinking is the mother of life. Critical thinking skills are one of the fundamental skills in the modern era. This study aims to examine the effect of the guided discovery model on students' critical thinking skills. This study uses an experimental method with a one group pree-test-post-test design with a population of IAIN Batusangkar students taking the sociology of religion course. The sample was determined by random sampling technique with a sample of 28 people. Data were collected using a scale-shaped instrument. Data processing with the help of SPSS .05 application. Prerequisite tests were carried out before data analysis, namely normality test and homogeneity test. Analyzed data using paired sample t test. The results showed the guided discovery model had a significant effect on students' critical thinking skills and it was proven that there was a significant difference between students' critical thinking skills before and after the application of the guided discovery model. The criteria for the significance of the results of the study were strengthened by the N-Gain value the data before and after treatment which was in the very good category.